Effects of enhanced temperature and ultraviolet B radiation on a natural plankton community of the Beagle Channel (southern Argentina): a mesocosm study - Moreau, S. (2014)
Marine planktonic communities can be affected by increased temperatures associated with global climate change, as well as by increased ultraviolet B radiation (UVBR, 280-320 nm) through stratospheric ozone layer thinning. We studied individual and combined effects of increased temperature and UVBR on the plankton community of the Beagle Channel, southern Patagonia, Argentina. Eight 2 m3 mesocosms were exposed to 4 treatments (with 2 replicates) during 10 d: (1) control (natural temperature and UVBR), (2) increased UVBR (simulating a 60% decrease in stratospheric ozone layer thickness), (3) increased temperature (+ 3°C), and (4) simultaneous increased temperature and UVBR (60% decrease in stratospheric ozone; + 3°C). Two distinct situations were observed with regard to phytoplankton biomass: bloom (Days 1-4) and post-bloom (Days 5-9). Significant decreases in micro-sized diatoms (>20 µm), bacteria, chlorophyll a, and particulate organic carbon concentrations were observed during the post-bloom in the enhanced temperature treatments relative to natural temperature, accompanied by significant increases in nanophytoplankton (10-20 µm, mainly prymnesiophytes). The decrease in micro-sized diatoms in the high temperature treatment may have been caused by a physiological effect of warming, although we do not have activity measurements to support this hypothesis. Prymnesiophytes benefited from micro-sized diatom reduction in their competition for resources. The bacterial decrease under warming may have been due to a change in the dissolved organic matter release caused by the observed change in phytoplankton composition. Overall, the rise in temperature affected the structure and total biomass of the communities, while no major effect of UVBR was observed on the plankton community.